Perceptions And Interests Of Young Entrepreneurs In Sharia-Based Business Finance - Wahyuni, Fitri; Bustami, Alex Wissalam (JPS (Jurnal Perbankan Syariah), 2024)
This study analyses the perception and interest of young entrepreneurs in Sharia-based business financing at BSI in Sungai Penuh City, Jambi. This study uses a qualitative approach with primary data from interviews. Interviews were conducted directly with six informants. The data analysis technique uses the Miles and Huberman approach with the following stages: data reduction, data presentation, verification, and conclusion. The results of the study indicate that the perception of young entrepreneurs towards Sharia-based loans is generally very positive; they understand the basic principles of Sharia in financing without interest and the application of profit sharing. Young entrepreneurs also recognize the benefits of sharia financing, such as easy access and simple procedures. On the other hand, the interest of young entrepreneurs in Sharia financing is still relatively low. This is due to the need for more socialization and support from Sharia financial institutions and limited financing options. Theoretically, this study can be used as a reference for relevant research in the future. Practically, this study can be a reference for Sharia financial institutions in designing marketing strategies and developing financing products that meet prospective customers' needs so that they can have a positive impact and increase interest and awareness of the importance of Sharia financing among young entrepreneurs.